Challenges and Opportunities of Interfaith Dialogue and Cooperation in a Globalized World in India - Intan, Amisha (Journal of Philosophy, Culture and Religion, 2024)
Purpose: The aim of the study was to investigate challenges and opportunities of interfaith dialogue and cooperation in a globalized world in India Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Interfaith dialogue and cooperation are essential for promoting peace, harmony, and mutual understanding in a globalized world. India, as a diverse and pluralistic country, faces both challenges and opportunities in this regard. Some of the challenges include communal violence, religious intolerance, and social exclusion of minority groups. Some of the opportunities include the rich heritage of religious diversity, the constitutional framework of secularism, and the civil society initiatives for interfaith engagement. Unique Contribution to Theory, Practice and Policy: Social identity theory, Communication accommodation theory & Constructive conflict resolution theory may be used to anchor future studies challenges and opportunities of interfaith dialogue and cooperation in a globalized world in India. Educational institutions and organizations should implement programs aimed at fostering empathy, communication skills, and cultural sensitivity among individuals engaging in interfaith dialogue. Governments and international organizations should allocate funding to support interfaith initiatives, both at the grassroots and global levels.